Coffee Chains Brewing Up the Taste Quotient of Indian Consumers: An Empirical Study in Delhi NCR - Kapoor, Deepa; Munjal, Alka (Indian Journal of Marketing, 2015)
Indians largely have been accustomed to drinking tea, and coffee has been considered as a drink for the high - end population. However, this notion is changing, and the coffee culture in India is flourishing with the entrance of local and international brands of coffee chains. In addition to serving hot and cold varieties of coffee and snacks, coffee shops provide a leisurely experience and space to bring people closer to each other. With increasing number of players entering in the café market, the competition is mounting, and creating a space in the minds of the customers will be an uphill task for these outlets. This research highlighted the perceptual mapping of four coffee chains, that is, Café Coffee Day, Costa Coffee, Barista, and Starbucks. With a sample of 120 respondents, this paper attempted to explore various factors that may influence the selection of a particular coffee shop, and in addition, the paper also examined the respondents' purpose of visiting the coffee shops. Discriminant analysis was applied to construct the perception map of the customers. The results revealed that product quality and ambience were the most important attributes affecting customers' decision making in selection of coffee outlets.